Islamic Thought, Religious Authority, and Ethical Formation in the Age of Digital Modernity: Contributions to the Sustainable Development Goals - Alwy Ahmed Mohamed; Ahmad Remanda; Mariam Elbanna; Muhammad Ndow; Qudra Bezibweki (Penerbit Hellow Pustaka, 2026)
Objective: This study aims to examine how Islamic thought, religious authority, and ethical formation are being reshaped in the age of digital modernity and to assess their contributions to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions). The research focuses on the ways digital platforms, algorithm-driven religious content, and emerging forms of online authority influence ethical reasoning, civic responsibility, and moral development within contemporary Muslim societies. Theoretical framework: The theoretical framework integrates classical Islamic epistemology (ʿilm, authority of the ʿulamāʾ, adab, and maqāṣid al-sharīʿah) with critical theories of power and knowledge, digital religion theory, and ethical governance frameworks. This interdisciplinary approach enables an analysis of how digital technologies mediate religious authority and ethical norms, and how these transformations intersect with global development agendas articulated in the SDGs. Literature review: The literature review covers three main bodies of scholarship: (1) classical and contemporary discussions on Islamic religious authority and ethical formation; (2) studies on digital religion, social media, and algorithmic governance; and (3) SDG-oriented research on education, institutional trust, and ethical sustainability. While existing studies acknowledge the growing influence of digital Islam, limited attention has been given to its implications for ethical development and sustainable governance from an Islamic perspective. Methods: This study adopts a qualitative research design combining discourse analysis of digital Islamic content, document analysis of policy and educational frameworks, and semi-structured interviews with Islamic scholars, educators, and Muslim youth. Data are analyzed thematically to identify patterns in the production of religious authority, ethical narratives, and their alignment with SDG-related objectives. Results: The findings reveal that digital modernity is simultaneously democratizing and fragmenting Islamic religious authority. While digital platforms expand access to religious knowledge and ethical discourse, they also challenge traditional structures of authority and risk promoting superficial or polarizing interpretations. Nevertheless, when guided by ethical frameworks grounded in maqāṣid al-sharīʿah, digital Islamic engagement has the potential to strengthen ethical education, civic responsibility, and institutional trust. Implications: The study highlights the need for ethically grounded digital Islamic education and responsible religious leadership to support sustainable development. By aligning Islamic ethical formation with SDG 4 and SDG 16, the research offers policy-relevant insights for educators, religious institutions, and development actors seeking to harness digital religion as a resource for peace, justice, and sustainable social development. Novelty: This study provides an original contribution by explicitly linking transformations in Islamic thought and religious authority under digital modernity to the Sustainable Development Goals, offering a normative and analytical framework that positions Islamic ethics as an active contributor to global development discourse.